Analysis of factors facilitating local farmers groups networks: a case study of Ga-Mothiba Village in Limpopo Province - Maredi, Nkhakha Maria (My University, 2008)
Farmer’s networks can be an effective means to contribute to sustainable agricultural development. Farmers can learn from each other, with each other, can act as a negotiating partner, invest collectively and involve relevant partners. However farmer’s networks are often confronted with barriers such as lack of institutional and organizational support. The main objective of this study was to analyze factors that facilitate local farmer’s group network in Ga- Mothiba village of Limpopo Province. Eight local groups were identified. The focus groups interviews were done with all the groups using a questioning route. Thereafter individual interviews were conducted with members from the groups using a questionnaire that was designed based on responses from the questioning route. Participatory Rural appraisal was done to assess the activities within the village. Groups were given a chance to identify factors pertaining to development in their village such as natural resource management (soil, vegetation and water), infrastructure, support from other stakeholders and communication coverage. The forum was formed out of the common interests that were obtained from the transect walk. Existing groups have been strengthened during the process while other informal groupings decided to be recognized as a local group. They’ve organized themselves, to be more effective in managing their natural resources, to expand their access to natural resources, to control and gain access to services, to lobby for their needs, and to make their voices heard in decision-making processes. The emergence of the forum resulted in a number of achievements. Farmers are able to exchange ideas and share experiences. The local forum gave farmers recognition and they’ve different support linkages and exposures. And this facilitates and promotes the development of new groups of farmers. The forum also had an opportunity to be part of the Limpopo Small-Scale Farmers Forum (LSAFF) and also as a member of the East and Southern African Small Scale Farmers Forum (ESAFF). Although the study indicated that there are benefits for farmers to network, management aspects of the network were found challenging. These aspects included balance leadership, collective responsibility and coherence of the group. Limited interest in these aspects may endanger the continuity of the network in the future especially when new members join in with different expectations. It has been recommended that there should be continuous field days, farmers days, local workshops as part of awareness campaigns so that farmers can exchange information and experiences. Extension should assist farmers in facilitation, identification, mobilisation and integrations of different types of knowledge. There’s also a need for monitoring and evaluation of farmers participation in development work and to analyse the impact of its interaction of farmers in development.
Thesis (M.Sc. ( Agricultural Extension)) -- University of Limpopo, 2008
Keywords: Farmer networks; Sustainable agricultural development; Ga-Mothiba Village; Farmers -- South Africa -- Limpopo; Agricultural development projects -- South Africa -- Limpopo